RELATIONSHIP OF BEHAVIOR WITH MOTHER'S VISIT TO INTEGRATED HEALTH CENTER - Ema Julia; Enda Silvia Putri (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2022)
Integrated Health Center is one of the efforts to improve health status in Indonesia with the main objective of reducing the Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR). Visits of toddlers in Arongan Village are getting lower, this is probably caused by several factors including knowledge, age, education, occupation, attitudes and actions. The purpose of this study was to determine the relationship between behavior and the mother's visit to the Integrated Health Center in Arongan Village. This research uses analytic research with cross sectional research design. The population in this study were all mothers unde Keywords: Knowledge, Attitude, Action, Integrated Health Center Visit.r five, amounting to 72 people. The research sample used a total sampling technique as many as 72 mothers of children under five. Data were analyzed using univariate and bivariate analysis and tested with the chi-square test. The analysis used in this research is univariate analysis and bivariate analysis. The results of this study are that there is a significant relationship between mother's knowledge and visits to Integrated Health Center (Pvalue = 0.022), there is a significant relationship between attitudes and mother's visits to Integrated Health Center (Pvalue = 0.017) and there is a significant relationship between actions and mother's visits to Integrated Health Center (Pvalue = 0.028). The conclusion is that there is a relationship between mother's knowledge, mother's attitude and mother's actions with visits to Integrated Health Center. Suggestions that can be put forward in this study are to improve the Integrated Health Center policy to attract mothers to attend activities held by the Integrated Health Center.